Inovasi “Daakian” Sebagai Transformasi Pelayanan Kartu Identitas Anak di Kabupaten Bojonegoro - Farras Dewi Yuanita; Kalvin Edo Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bojonegoro Regency has a low rate of Kartu Identitas Anak (Child Identity Card) issuance, reaching only 34.75% of the national target, which should have been 50% in 2023. The factors hindering the issuance of Kartu Identitas Anak in Bojonegoro Regency include a lack of public awareness, the absence of regulations requiring the use of Kartu Identitas Anak for any child-related identification purposes, a lack of support from other institutions or agencies, and inadequate infrastructure. To address this, Dinas Kependudukan dan Pencatatan Sipil (the Civil Registry Office of Bojonegoro Regency) launched the